(untitled) (Revista Inclusiones, 2020)
The object of the study is nationalism as a phenomenon of human civilization. The subject is the trends of Atlantic-European nationalism. The authors set a goal, based on the analysis of methodological approaches to the nature of nationalism, to reveal its main radical trends of manifestation in Europe and the USA. The authors pay special attention to the study of the duality of the manifestation of nationalism in various regions of the world. On the example of individual countries, it is shown that nationalism in its manifestation in society can play both a constructive role, acquiring a patriotic orientation, and a destructive one, performing the function of a catalyst for escalating social tension. The theoretical base includes scientific works on the analysis of the genesis and manifestation of nationalism, the results of opinion polls and statistical data. The methodological basis of the study includes a retrospective analysis of scientific works revealing the nature of nationalism, as well as a systematic approach that allows the authors to identify and substantiate the role of identity and unity in the genesis of nationalism. The epistemological potential of statistical and sociological methods of quantitative and qualitative research makes it possible to interpret correctly the current scientific research results regarding the hypothesis put forward by the authors. The novelty of the work and its results are determined by the original approach to identifying the radical trends of modern Atlantic-European nationalism, studying its systemic ties with the sociopolitical situation in Europe and the USA. The results obtained in the study allow the authors to conclude that modern Atlantic-European nationalism has gained populism among the population, has firmly entered the sociopolitical sphere of society and power structures and has a negative impact on the development of Europe and the USA, applying radical methods of achieving the goal.